Political risk and export promotion: evidence from Germany - Christoph Moser; Thorsten Nestmann; Michael Wedow (Deutsche Bundesbank, 2006)
Political risk represents an important hidden transaction cost that reduces international trade. This paper investigates the claim that German public export credit guarantees (Hermes guarantees) mitigate this friction to trade flows and hence promote exports. We employ an empirical trade gravity model, where we explicitly control for political risk in the importing country in order to evaluate the effect of export guarantees. The idea behind export promotion through public export credit agencies (ECAs) is that the private market is unable to provide adequate insurance for all risks associated with exports. As a consequence, firms' export activities are limited in the absence of insurance provision. Using a novel data set on guarantees we estimate the effect of guarantees in a static and dynamic panel model. We find a statistically and economically significant positive effect of public export guarantees on exports which indicates that export promotion is indeed effective. Furthermore, political risk turns out to be a robust determinant of exports and hence should be taken into account in any empirical model of trade.
Keywords: C23; H81; F13; 330; public export credit guarantees; political risk; panel regression; Exportgarantie; Wirtschaftspolitische Wirkungsanalyse; Export; Schätzung; Deutschland; Länderrisiko; Welt